Long Noncoding RNA TRPM2-AS Promotes the Growth, Migration, and Invasion of Retinoblastoma via miR-497/WEE1 Axis - Li, Aipeng; Yang, Jingpu; Zhang, Ting; Li, Lin; Li, Miyang (Frontiers in Pharmacology, 2021)
Long noncoding RNAs (lncRNAs) exhibit vital roles in many types of cancer, including retinoblastoma (RB), the most common primary intraocular malignancy tumor of infancy. A novel lncRNA TRPM2-AS has been demonstrated to be related to multiple cancers; however, its role in RB remains unclear. Here, we aimed to investigate the function of TRPM2-AS in RB. In this study, TRPM2-AS expression in 35 human RB tissues and RB cell lines was detected by real-time PCR. And, the relationship between its expression and clinicopathological characteristics of RB patients was analyzed. RB cells’ proliferation, migration, invasion, apoptosis, and cell cycle were explored after silencing TRPM2-AS. The mechanism of TRPM2-AS in RB was focused on miR-497/WEE1 axis. Additionally, the role and mechanism of TRPM2-AS were confirmed in a xenograft mouse model. We found TRPM2-AS expression was enhanced in RB tissues and cells. And, higher TRPM2-AS expression was related to advanced clinical stage and optic nerve invasion in patients. Downregulation of TRPM2-AS significantly inhibited proliferation, migration, and invasion, elevated apoptosis, attenuated G2/M phase arrest in RB cells, and suppressed tumor growth in vivo. TRPM2-AS acted as a ceRNA for miR-497 to positively regulate WEE1 expression. miR-497 inhibitor or WEE1 overexpression dramatically reversed the effects of TRPM2-AS downregulating on the malignant phenotypes of RB cells. Therefore, TRPM2-AS is an oncogenic lncRNA in RB, and it functions largely through the miR-497/WEE1 pathway. Despite the limited sample size, this study indicates that TRPM2-AS may be a candidate target in RB therapies.